Piano sonata no. 32, op. 111, edited by Winkler, with Winkler's metronome markings - Beethoven, Ludwig van, 1770-1827 (2025)
Piano sonata no. 32 in C minor, op. 111, edited by Winkler, with Winkler's metronome markings